Optic nerve sheath diameter and severity of central nervous infection - Dewi, Anggun Puspita; Lukmanul Hakim, Dzulfikar Djalil; Rahayuningsih, Sri Endah; Risan, Nelly Amalia; Ghrahani, Reni; Adrizain, Riyadi (Indonesian Pediatric Society, 2023)
Background Central nervous system (CNS) infection affects the brain, and can cause cerebral edema, increased intracranial pressure (ICP), cerebral herniation, and death. Measurement of the optic nerve sheath diameter (ONSD) by ultrasound is a new, non–invasive examination to predict ICP, with high sensitivity and specificity.Objective To analyze for a possible association between ONSD measured by ultrasonographic examination and severity of CNS infection. Methods This cross–sectional study was performed in the Pediatric Department of Hasan Sadikin Hospital, Bandung, West Java. Subjects were chosen by consecutive sampling. We measured ONSD, examined clinical manifestations, as well as performed a cerebrospinal fluid (CSF) study and imaging of CNS infection. Data analysis was done by paired T–test and one–way ANOVA, followed by Tukey test on significant variables. Results Subjects consisted of 32 children with CNS infection. The most common clinical symptoms were fever, decreased consciousness, and nuchal rigidity. Bivariate analysis revealed strong positive associations between ONSD and Glasgow Coma Scale (GCS), increased protein levels in CSF, and type of CNS infection. Conclusion Larger ONSD is significantly associated with lower GCS, increases CSF protein, and particular CNS infections. The ONSD is also associated with meningitis tuberculosis grade III, with a higher mean ONSD of both eyes compares to other CNS infections. Hence, the higher the ONSD, the more severe the degree of CNS infection.